Good Corporate Governance At Basic Industry and Chemical Company Affecting Profitability in Review from the Aspect of Earning Per Share - Nasfi Nasfi (International Journal of Management and Business Applied, 2022)
The purpose of this study was to determine the effect of institutional ownership to determine the effect of board size partially, to determine the effect of the composition of commissioners partially to the company's profitability as proxied by Earning Per Share and to determine the effect of the number of audit committees partially to profitability as proxied by Earning Per Share. The research method uses a purposive sampling technique with a representative sample of 45 companies engaged in the basic industry and chemical sector listed on the Indonesia Stock Exchange from 2018 to 2021, data processing analysis with descriptive statistical analysis with panel data estimation of engineering models. and presented in qualitative and quantitative forms. Institutional Ownership has a coefficient value of -0.468 and a p-value t-stat of 0.298 which means it has a negative and insignificant effect, the Board of Directors has a coefficient value of -0.044 and a p-value t-stat of 0.904 which means a negative effect and not significant, the Independent Commissioner has a coefficient value of 0.647 and a p-value t-stat of 0.0000 which means a positive and significant effect and the Audit Committee has a coefficient value of -1.0289 and a p-value of t-stat 0, 0000 which means negative but significant. The novelty of this study is the existence of a partial audit committee variable from other studies.